Tesla: beyond overvalued - can the market price innovation? - Viegas, António Maria Gião Piçarra Ferreira (2021)
In the upcoming ten years, the automotive Industry will undergo many changes due to various factors. Tesla is certainly at the forefront of the Industry, as we can confirm by the complete dominance of its vehicles in the EV market; it remains to be seen whether they will deliver the promises amounts. With the addition of the two new Giga factory's and the constant improvement of efficiency, we believe Tesla will finally start delivering at their expected rate, raising their market share and profitability.